Docetaxel versus abiraterone for metastatic hormone‐sensitive prostate cancer with focus on efficacy of sequential therapy. Issue 6 (20th January 2023) - Yanagisawa, Takafumi; Hata, Kenichi; Narita, Shintaro; Hatakeyama, Shingo; Mori, Keiichiro; Yata, Yuji; Sano, Takayuki; Otsuka, Takashi; Hara, Shuhei; Miyajima, Keiichiro; Enei, Yuki; Fukuokaya, Wataru; et al.
Abstract: Purpose: We aimed to assess the oncologic efficacy of combining docetaxel (DOC) versus abiraterone (ABI) with androgen deprivation therapy (ADT) in patients with high‐risk metastatic hormone‐sensitive prostate cancer (mHSPC), with a focus on the efficacy of sequential therapy, in a real‐world clinical practice setting. Methods: The records of 336 patients who harbored de novo high‐risk mHSPC, based on the LATITUDE criteria, and had received ADT with either DOC ( n  = 109) or ABI ( n  = 227) were retrospectively analyzed. Overall survival (OS), cancer‐specific survival (CSS), progression‐free survival (PFS), including time to castration‐resistant prostate cancer (CRPC), time to 2nd‐line progression (PFS2), and 2nd‐ and 3rd‐line PFS, were compared. We used one‐to‐two propensity score matching to minimize the confounders. The differential efficacy of 2nd‐line therapy based on agents in each arm was evaluated using the unmatched cohort as an additional interest. Results: After propensity score matching, 86 patients treated with DOC + ADT and 172 with ABI + ADT were available for analyses. The 3‐year OS and CSS for DOC versus ABI were 76.2% versus 75.1% ( p  = 0.8) and 78.2% versus 78.6% ( p  = 1), respectively. There was no difference in the median PFS2 (49 vs. 43 months, p  = 0.39), while the median time to CRPC in patients treated with ABI was significantly longer compared to those treated with DOC (42 vs. 22 months; p  = 0.006). The median 2nd‐line PFS (14 vs. 4 months, p  < 0.001) and 3rd‐line PFS (4 vs. 2 months, p  = 0.012) were significantly better in the DOC group than in the ABI group. Among the unmatched cohort, after ABI for mHSPC, the median 2nd‐line PFS did not differ between the patients treated with DOC and those treated with enzalutamide as 2nd‐line therapy (both 3 months, p  = 0.8). Conclusions: ADT with DOC or ABI has comparable oncologic outcomes in terms of OS, CSS, and PFS2 in patients with de novo high‐risk mHSPC. Compared to DOC, ABI resulted in longer time to CRPC but worse 2nd and 3rd‐line PFS. Further studies are needed to clarify the optimal sequence of therapy in the upfront intensive treatment era.